Dessensibilização dos nervos palmares em eqüinos: estudo comparativo experimental do álcool benzílico 0,75% e álcool etílico absoluto (95,5% PA) - Escodro, Pierre Barnabé [UNESP] (2004)
To test the clinical and histopathological effects of two chemical neurolytics, the left forelimb of ten normal horses were shod with a designed shoe adaptted with 5 screws to produce solar pressure and induced lameness. After gait and lameness score analysis, the lateral and medial branchs of the left palmar nerve of 5 horses was injected with 5 ml of 0,75% benzyl alcohol -Sarapin -(Group A) and 5 horses was injected with 5 ml of pure ethyl alcohol or absolute alcohol (Group B). The animals were submitted to lameness evaluation and solar sensibility tests during the next months. In the Group A, which was injected with benzyl alcohol -Sarapin , the solar pain returned 5 months latter while in the Group B, injected with ethyl alcohol (ethanol or absolute), the solar surface was still desensitized 6 months latter. The histopathological examination of the palmar nerve showed that the perineural injection of benzyl alcohol 0,75% - Sarapin , (Group A), resulted in axonotmesis, characterized by axonal nerve degeneration, without disruption of connective tissue elements (endo, peri and epineurium), with good prognosis for recovery the nerve conduction. In the Group B, the perineural injection of ethyl alcohol absolute (ethanol), resulted in neurotmesis, characterized by disruption of all the axon and supporting connective tissue structures, with poor prognosis for nerve regeneration. It was concluded that chemical neurolysis with alcohol is an option for temporary or permanent nerve blocks in horses but the minimum concentration and number of injections required for neurolysis must be established.